PENGARUH PELAKSANAAN PRE DAN POST CONFERENCE TERHADAP PENDOKUMENTASIAN ASUHAN KEPERAWATAN - Rezkiki, Fitrianola; Febrina, Wiwit; Anggraini, Devi (Universitas Fort De Kock Bukittinggi, 2019)
Nursing documentation is a record that contains all the data needed to determine nursing diagnoses, planning, actions and evaluations that are arranged in a systematic, valid, and morally and legally responsible manner. Based on a preliminary study with a sample of 10 documentation of internal space medical records taken randomly only 4 (40%) were completely filled and 6 (60%) incomplete. This study aims to determine the effect of pre and post conference services on documenting nursing care. This study uses a pre-experimental design with one-group pretest-posttes design. The method of data collection is using observation sheets. Samples are taken with a simple random sampling system of 10 samples. The results of the study based on the Kolmogrov-smirnov test observations were carried out before and after being given a pre and post conference treatment of 10 statuses obtained a p-value of 0,000. The conclusion of this study is that there is an influence of the implementation of pre and post conference on the documentation of nursing care.Keywords: Documentation, Pre and post conference